Data Traceability and Digital Quality Infrastructure in Africa: A Systematic Review of Export Compliance for EU, US, and East Asian Markets - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
The current scenario of international trade is undergoing a major change, where data traceability and DQI are becoming crucial factors that will determine access to markets for products from Africa. The current literature review aims to systematically review existing literature on the challenges faced by African exporters to meet the rigorous compliance standards in Europe, the USA, and East Asia. It is observed that the main barriers faced by African producers include poor metrology systems, supply chain issues, poor digital connectivity, and high compliance costs of about USD 20,000 for small and medium-sized enterprises. Such issues are further complicated by increasingly complex regulatory regimes like the EU Deforestation Regulation (EUDR), Carbon Border Adjustment Mechanism (CBAM), and Corporate Sustainability Due Diligence Directive (CSDDD), which require a new level of supply chain visibility, geolocation confirmation, and verified carbon measurement. While continental bodies like the Pan African Quality Infrastructure (PAQI) and Intra-Africa Metrology System (AFRIMETS) offer institutional frameworks, there remain substantial gaps in implementation. Innovations at the national level, such as Ethiopia’s Coffee Traceability and Management System, show the possibilities of customized solutions. The paper has been able to highlight important gaps in the literature and provide some recommendations that will be helpful for policymakers, exporters, and development partners. The study claims that the use of digital technology to improve the quality of infrastructure, harmonize standards, and build capacity could help turn compliance into an advantage for African exporters. Considering the fact that the deadline for EUDR compliance is fast approaching in December 2026, it is imperative to act now to ensure Africa's place in global value chains.